2016
DOI: 10.1177/0897190016630408
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bleeding Events Requiring Hospitalization in Patients With Atrial Fibrillation Receiving Dabigatran, Warfarin, or Antiplatelet Therapy

Abstract: Anticoagulation with dabigatran was associated with an overall increased occurrence of bleeding requiring hospital admission compared to warfarin. GI bleeding was more prevalent with dabigatran and antiplatelets than with warfarin. There were more intracranial hemorrhages seen in the warfarin group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Moreover, the selection of either an anticoagulant or an antiplatelet agent should be carefully determined in FD patients because dabigatran, similar to warfarin, confers a higher risk of life-threatening bleeding events than antiplatelet agents. [ 10 ] A recent systematic review indicates that administration of another anticoagulant, apixaban, does not confer an increased bleeding risk like dabigatrin. [ 11 ] Therefore, in FD patients who require anticoagulation, apixaban may be a preferred anticoagulant, and antiplatelet agents should be considered as an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the selection of either an anticoagulant or an antiplatelet agent should be carefully determined in FD patients because dabigatran, similar to warfarin, confers a higher risk of life-threatening bleeding events than antiplatelet agents. [ 10 ] A recent systematic review indicates that administration of another anticoagulant, apixaban, does not confer an increased bleeding risk like dabigatrin. [ 11 ] Therefore, in FD patients who require anticoagulation, apixaban may be a preferred anticoagulant, and antiplatelet agents should be considered as an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Overall, patients taking warfarin have signi cantly more bleeding events than patients taking other anticoagulants (P<0.001). [5][6][7] Numerous algorithms that are based on patient factors and genetic variants have been established by multivariate linear regression with the aim of reducing the risk of bleeding during the initial days of warfarin administration. [8] In 2007, we [9,10] created an algorithm for daily warfarin dose requirements so that appropriate warfarin maintenance doses could be calculated easily.…”
Section: Introductionmentioning
confidence: 99%
“…However, several cases of serious hospitalized bleeds associated with dabigatran have been reported . When comparing dabigatran with warfarin, the literature provides inconsistent results, as some studies found a higher risk of hospitalized bleeding with dabigatran over warfarin , whereas some studies reported no increased risk . Indeed, dabigatran works rapidly following its initiation ; hence it may lead to more early‐onset bleeds.…”
Section: Introductionmentioning
confidence: 99%